Effects of Different Types of Corrective Feedback on Receptive Skills in a Second Language: A Speech Perception Training Study. Issue 4 (17th February 2016) - Lee, Andrew H.; Lyster, Roy
Abstract: This study investigated the effects of different types of corrective feedback (CF) provided during second language (L2) speech perception training. One hundred Korean learners of L2 English, randomly assigned to five groups ( n = 20 per group), participated in eight computer‐assisted perception training sessions targeting two minimal pairs of English vowels. Four treatment groups each received a different type of CF; three groups received one of three types of auditory CF and a fourth group received a visual type of CF; the control group did not receive CF. Results of pretests, immediate posttests, and delayed posttests showed that, in comparison to the control group, the groups that received auditory CF improved significantly in trained over untrained words, whereas the group that received visual CF fared less well. These results are discussed in terms of the benefits of auditory CF types, especially CF combining target and nontarget forms. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .